THE LEADERSHIP OF THE SUB-DISTRICT HEAD AT THE RAREN BATUAH SUB-DISTRICT OFFICE, EAST BARITO REGENCY - Arpandi Arpandi; Arif Budiman; Ahmad Baihaqi (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: Leadership is a behavior with a specific purpose to influence the activities of group members to achieve common goals designed to provide individual or organizational benefits, so that in an organization leadership is a very important factor in determining the achievement of the goals set at the Raren Batuah District office, Barito Regency East, has the problem of the lack of accuracy of the sub-district head in giving the delegation of authority, the lack of leadership oversight of employees in terms of time discipline, the sub-district head is often not in place seen from the sub-district head who is rarely in the office environment. Based on this, this study aims to find out how the sub-district leadership is at the Raren Batuah District office, East Barito Regency and the factors that influence it. Method: This study used a qualitative approach with a qualitative descriptive type. Data collection techniques through interviews, observation/observation of literature studies and documentation. Sources of data were taken from informants using a purposive method, totaling 10 people. To test the credibility of the data using triangulation techniques and conducting member checks. Results: The results showed that the leadership of the sub-district head at the Raren Batuah sub-district office, East Barito district, was quite good. This is the sub-district head in his leadership in the sub-district, such as the Instruction Function in coordination and direction is quite good, the Consultation Function in coordination and decision-making is quite good, the Participation Function in the presence of meeting leaders and Cooperation is quite good, the Delegation Function in Delegation of authority is still not good, the control function in supervision and work discipline is still not good. Besides that, the factors that influence the leadership of the sub-district head at the Raren Batuah sub-district office are divided, namely driving factors such as decision-making, communication, and the presence of leaders in meetings which are quite good, while the inhibiting factors are the lack of supervision, the lack of firmness and discipline of the sub-district head and the inaccuracy of the sub-district head in providing delegation of authority so that the maximum service is lacking. Novelty: This study aims to find out how the sub-district leadership is at the Raren Batuah District office, East Barito Regency and the factors that influence it, especially related to delegation of authority, supervision, work discipline, and the presence of leaders in the office environment.